Biomass derived Nitrogen, Sulphur, and Phosphorus self-doped micro-meso porous carbon for high-energy symmetric supercapacitor – With a detailed study of the effect of different current collectors. (10th December 2022) - Nanda, Om Priya; Badhulika, Sushmee
Abstract: A cost-effective and high-performance supercapacitor with large specific energy is still a major challenge in the field of energy research. Here, we report a green and inexpensive synthesis of Nitrogen, Sulphur, and Phosphorus self-doped activated carbon from Euphorbia milii plant waste via a two-step KOH activation process for supercapacitor applications. The optimized EMAC (at 700 °C activation) exhibits distinctive stacking of carbon nanosheets with micro-meso pores-like morphology and displays a 2349 m 2 /g surface area obtained via FESEM and BET analysis respectively. So the electrochemical behavior of EMAC-700 with different current collectors (Stainless Steel, Graphite Paper, and Nickel Foam) in a half cell with 6 M KOH is optimized and Nickel foam showed the highest 474.3 F/g specific capacitance at 1 A/g. Furthermore, symmetric cell delivered an excellent specific capacitance of 290.3 F/g at 0.5 A/g with high energy density of 39.75 Wh/kg at 496.5 W/kg. On top of this, the cell also showed 90.23 % capacitance retention even after 20k long charging and discharging cycles at 20 A/g. This remarkable outcome of EMAC-700 could be because of parallel stacking of graphitic layers and the existence of heteroatoms namely nitrogen, sulphur, and phosphorus which increase the surface wettability and indorses defects in the porous carbon to increase the conductivity and capacitive effect. These results demonstrate that self-heteroatom-doped EMAC has an exceptional ability for sustainable and regenerative energy storage devices. Graphical abstract: Unlabelled Image Highlights: Nitrogen, Sulphur, and Phosphorus heteroatom self-doped porous carbon obtained from Euphorbia milii plant waste Current collector optimization showed high electrocatalytic activity of Nickel foam. Symmetric cell delivered a high energy density of 39.75 Wh/kg at power density of 496.5 W/kg.